Synthesis of New Visnagen and Khellin Furochromone Pyrimidine Derivatives and Their Anti-Inflammatory and Analgesic Activity - Ameen Ali Abu-Hashem; Mohamed M. Youssef (Molecules, 2011)
6-[(4-Methoxy/4,9-dimethoxy)-7-methylfurochromen-5-ylideneamino]-2-thioxo-2,3-dihydropyrimidin-4-ones 1a,b were prepared by reaction of 6-amino-2-thiouracil with visnagen or khellin, respectively. Reaction of 1a,b with methyl iodide afforded furochromenylideneaminomethylsulfanylpyrimidin-4-ones 2a,b. Compounds 2a,b were reacted with secondary aliphatic amines to give the corresponding furochromen-ylideneamino-2-substituted pyrimidin-4-ones 3a–d. Reaction of 3a–d with phosphorus oxychloride yielded 6-chlorofurochromenylidenepyrimidinamines 4a–d, which were reacted with secondary amines to afford furochromenylideneamino-2,6-disubstituted pyrimidin-4-ones 5a–d. In addition, reaction of 5a–d with 3-chloropentane-2,4-dione gave 3-chloro-furochromenylpyrimidopyrimidines 6a–d. The latter were reacted with piperazine and morpholine to give 1-(furochromenyl)-pyrimidopyrimidine-3,6,8-triylpiperazines or -3,6,8-triylmorpholines 7a–d. The chemical structures of the newly synthesized compound ware characterized by IR, 1H-NMR, 13C-NMR and mass spectral analysis. These compounds were also screened for their analgesic and anti-inflammatory activities. Some of them, particularly 3–7, exhibited promising activities.